Household Firewood Utilization Around the Hlathikulu Forest Reserve, South Africa - Vasicek, Caroline Anne; Gaugris, Jerome Yves (Ethnobotany Research and Applications, 2014)
<span style="font-size: 11.0pt; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold; mso-bidi-font-style: italic;" lang="EN-GB">A study to define firewood use and sustainability was commissioned by South Africa’s Kwazulu-Natal nature conservation authorities to define current use around a small afromontane forest reserve situated in the Maputaland – Pondoland – Albany biodiversity hotspot and resource availability within that reserve in order to plan the delivery of alternatives and preserve the forest. As a step in this process, a total of 121 rural households were surveyed to define current use patterns. The results regarding firewood particulars are presented here for the first time. Rural communities used and average of 134 firewood bundles per year, representing an annual volume of 25.4 m3 firewood. Firewood bundles lasted six days in summer and two days in winter. While 29 woody species were used, six species constituted the bulk of utilisation (70.8% of volume). Among these, Diospyros dichrophylla (5th position, 7.90% of volume used) is an abundant rapidly growing shrub occurring on degraded forest sections or fallow fields, with potential as an alternative firewood resource. The study results highlight the reliance on firewood (>90% households).